Essentials of meteorology : - Ahrens, C. Donald (Thomson Brooks/Cole, 2008)
This updated and enhanced Fifth Edition of Essentials of meteorology is written by the widely read and authoritative author in introductory meteorology-Donald Ahrens. Ahrens's ability to explain relatively complicated ideas in a student-friendly, manageable fashion will allow you to easily visualize the principles of meteorology. Essentials of meteorology is completely updated with over 250 new images and figures and the latest research and coverage. This new edition is accompanied by a self-paced tutorial system--CengageNOW for Essentials of meteorology. CengageNOW is Web-based, assessment-driven, completely flexible, and contains a wealth of book-specific interactivities. It offers a personalized study plan based on your assessment results, helping you focus on the concepts you don't yet understand.